(3aQhb GddZGJ aj GdJejjR Hjf eaGO GdcdeGJs - (3fhQ GdOjf Hf fYeI Gddg GdMSjfj GdLRGFQjs
(3ChdgG (B:s
(3GdMeO ddg GdPi ef Ydi Phi GdCdHGH HedGMI GdHjGf hHYO , ajbhd Cf Yde GddZI ef CYXe eG jMJGL Edjg GdWGdH hjeG SFd HYV GdWdHI Yf GdaQb Hjf GdcdeJjf s
(3BNQgG (B:s
(3ef HGH GdgGA (B: (3GdgOjI hGdgHI bhdg (B: (3heYdhe Cf GdfHi Udi Gddg Ydjg hSde cGf jJUQa ajg hjedcg ZjQg ef RhLGJg hZjQgf jbhd LGeY GdcJGH gPG eG JjSQ di ai gPG GdhbJ LeYg s
(3hCJHY GdeDda eGOI GdcJGH HNGJeI ef aUhd eJfhYI djSJ efgG hgj ai fMh (B58 (3hQbIs
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdKGfj YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA GdChd (B- (3bSe GdKGfi (B- (3U (B173 s
Keywords: (3GddZIs